SEKOLAH ORANG TUA QUR’ANI: PENGUATAN POLA ASUH ISLAMI DALAM MENDUKUNG PERKEMBANGAN ANAK USIA DINI - Devi Sulaeman; Kurniasih; Abdul Fatah; Saniyya Putri Hendrayana; Deden Deni Mahendra (Jurnal Pengabdian Indonesia (JPI), 2026)
Social and digital transformations have impacted early childhood parenting patterns, necessitating the strengthening of the family's role as the foundation for Islamic-based character education. This community service activity aims to improve literacy and practice of Islamic parenting through the Quranic Parent School program at the Merpati Early Childhood Education Post in Kutawaluya District. The program is designed to build synergy between schools and families in supporting the social-emotional and spiritual development of early childhood. The method used is a community-based participatory approach with stages of needs identification, joint action planning, parenting class implementation, and periodic reflection and evaluation. Activities are implemented through workshops, reflective discussions, simulations of Islamic parenting practices, and the establishment of a parent forum as a forum for program sustainability. The results of the activity indicate an increase in parents' understanding of the concepts of fitrah (natural nature) and adab (good manners), changes in communication patterns to be more empathetic, and consistent habits of worship and restrictions on gadgets at home. Further impacts are seen in increased discipline and emotional regulation of children at school and the formation of a Quranic family learning community. The implications of this activity confirm that strengthening Islamic parenting through the Quranic Parent School model is effective in encouraging family-based social transformation and has the potential to be replicated in other PIAUD institutions with similar characteristics.